Data Augmentation via Latent Diffusion Models for Detecting Smell-Related Objects in Historical Artworks - Sheta, Ahmed; Zinnen, Mathias; Sindel, Aline; Maier, Andreas; Christlein, Vincent (Lecture Notes in Computer Science, 2026)
Finding smell references in historic artworks is a challenging problem. Beyond artwork-specific challenges such as stylistic variations, their recognition demands exceptionally detailed annotation classes, resulting in annotation sparsity and extreme class imbalance. In this work, we explore the potential of synthetic data generation to alleviate these issues and enable accurate detection of smell-related objects. We evaluate several diffusion-based augmentation strategies and demonstrate that incorporating synthetic data into model training can improve detection performance. Our findings suggest that leveraging the large-scale pretraining of diffusion models offers a promising approach for improving detection accuracy, particularly in niche applications where annotations are scarce and costly to obtain. Furthermore, the proposed approach proves to be effective even with relatively small amounts of data, and scaling it up provides high potential for further enhancements. The source code for data generation and downstream evaluation is available at https://github.com/ultiwinter/MT_DA_LDM_OD.
CRIS-Team Scopus Importer:2026-01-26
Keywords: Artwork; Contextual Inpainting; ControlNet; Data Augmentation; Diffusion Models